Spectral Analysis of Confined Cylinder Wakes - Wilson Lu; Leon Chan; Andrew Ooi (Fluids)
Bluff body flows, while commonly assumed to be isolated, are often subject to confinement effects due to interactions with nearby objects. In this study, a simple approximation of such a flow configuration is considered, where a cylinder is placed symmetrically within an infinite channel. The presence of walls implies the wake is physically confined and introduces interactions between the wake and the boundary layer along the wall. To isolate the effect of confinement, simulations are conducted with slip channel walls, removing the boundary layers. Comparisons of flow statistics between simulations of slip and no-slip channel walls show minor differences at a low blockage ratio, <semantics>β</semantics> (defined as the ratio of cylinder diameter to channel height), while for larger blockage ratios, the differences are significant. Spectral analysis is also performed on the wake and shear layers. At the lowest blockage, <semantics>β=0.3</semantics>, little modification is made to the wake, and we find that Kármán vortices are one-way coupled to the boundary layers along the walls. For <semantics>β=0.5</semantics>, wall–wake interactions are determined to significantly contribute to wake dynamics, thus to two-way coupling Kármán vortices and the wall boundary layers. Finally, for <semantics>β=0.7</semantics>, the absence of Kármán shedding couples Kelvin–Helmoltz vortices in the shear layer, separating off the cylinder to the wall boundary layer.